Biomarkers of hepatocellular synthesis in patients with decompensated cirrhosis - Gurbuz, Berivan; Guldiken, Nurdan; Reuken, Philipp; Fu, Lei; Remih, Katharina; Preisinger, Christian; Brůha, Radan; Leníček, Martin; Petrtýl, Jaromír; Reissing, Johanna; Aly, Mahmoud; Fromme, Malin; et al. (Hepatology international, 2023)
BACKGROUND AND AIM: Since hepatocytes produce majority of serum proteins, patients with cirrhosis display substantial alterations in the serum proteome. The aim of the current study was to characterize these changes and to study the prognostic utility of hepatocellular proteins available in routine clinical testing. METHODS: Sera from 29 healthy controls and 43 patients with cirrhosis were subjected to untargeted proteomic analysis. Unsupervised hierarchical clustering was performed with Perseus software and R. Ingenuity pathway analysis (IPA) suggested upstream regulators that were validated in liver tissues. The behavior and prognostic usefulness of selected biomarkers was investigated in 61 controls and 285 subjects with decompensated cirrhosis. RESULTS: Proteomics uncovered 65 and 16 hepatocellular serum proteins that are significantly downregulated or upregulated in patients with cirrhosis vs. controls. Hierarchical clustering revealed two main clusters and six sub-clusters. IPA identified HNF4α and IL-6 as the two major upstream regulators that were confirmed by hepatic gene expression analyses. Among pseudocholinesterase, transferrin, transthyretin, albumin, and apolipoprotein AI (Apo-AI), Apo-AI was the best predictor of 90-days transplant-free survival (AUROC 0.678; p = 0.0001) and remained an independent predictor in multivariable Cox independently of the presence of acute-on-chronic liver failure. CONCLUSION: Our study reveals cirrhosis-associated changes in hepatocellular serum proteins and underlying transcription factors. Serum apolipoprotein AI may constitute a useful prognostic adjunct in patients with decompensated cirrhosis.
Keywords: apolipoprotein A-I; Liver Cirrhosis; Hepatocyte nuclear factor; biologické markery; Blood Proteins; Biomarkers; fibróza; prognóza; Carcinoma, Hepatocellular; Interleukin; Fibrosis; proteomika; krevní proteiny; lidé; jaterní cirhóza; Humans; Mass spectrometry; hepatocelulární karcinom; Apolipoprotein A-I; Prognosis; Proteomics; Liver Neoplasms; Decompensated cirrhosis; nádory jater